Genome-wide characterization and expression divergence of voltage-dependent anion channel (VDAC) in upland cotton (Gossypium hirsutum L.) in response to abiotic stresses - Akram, Umar; Ahmad, Ali; Shah, Muhammad Nadeem; Ahmad, Furqan; Baber, Muhammad; Altaf, Muhammad Tanveer; Rahman, Muhammad Aneeq Ur; Albayrak, Önder (Frontiers in Plant Science, 2025)
Voltage-dependent anion channels (VDACs) are proteins present at the outer membrane of mitochondria that are involved in stress response, such as drought and salt, signal transduction, and cellular metabolism. The role of the VDAC gene family in other crops has been identified, but its role in cotton has been uncharacterized. In this study, a genome-wide study was conducted in upland cotton (G. hirsutum L.) under drought and salt stresses. We identified 18 GhVDAC genes and mapped them using the MG2C online tool. The random distribution of GhVDAC genes was determined using the GSDS server for their intron-exon structure. Phylogenetic analysis using MEGA. 11 software constructed the phylogenetic tree by the maximum likelihood method of 14 different species with 66 VDAC genes, which were distributed across four clades. All p. patens VDAC genes were present in a single clade, and 10 GhVDAC genes were found in clade IV. Ten motifs were identified, and motif 9 was absent in GhVDAC3, GhVDAC9, GhVDAC10, GhVDAC11, and GhVDAC18. Motif 10 was present in only two genes, GhVDAC5 and GhVDAC14. Promoter analysis revealed cis-elements involved in hormone and stress response. Synteny and circos analysis revealed orthologous gene duplication events and evolutionary relationships. In-silico expression mapping was used to identify candidate genes, and then qRT-PCR was done for validation of GhVDAC6, GhVDAC11, GhVDAC13, and GhVDAC15 genes. In conclusion, this is a genome-wide study on the VDAC gene family in cotton under drought and salt stress that provides insights into their structure, evolutionary relationship, and molecular mechanism, and this study lays the theoretical foundation for future breeding programs to develop resistant crops for drought and salt stress.